Perancangan Video Company Profile Café 89 Degrees Coffee & Roastery - Deli Deli; Tony Wirawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Cafe has been a chosen place especially for teenagers up to adults as a place to hangout and dine in. Numerous café established has made micro, small and medium enterprises competitions fiercer than ever, by café services to food menus. The importance of promotion can increased by promoting with mouth to mouth, up to promoting in social media to attract more people to visit the café. Promotion is a method to make consumer attention towards a brand or brand awareness. Therefore, micro, small, and medium enterprises must have a video media as a tool to promote its business. With company profile video to promote its business name towards people. This article explains the process of implementing Community Service Project by Universitas Internasional Batam student for 89 Degrees Coffee & Roastery café. Writer will develop company profile video as a tool that will be used as promotion on one of many social media which is Instagram, using cinematography technique. Writer expects after the implementation of producing a Company Profile Video will increase the popularity & the sales of 89 Degrees Coffee & Roastery café